2013
DOI: 10.1155/2013/204259
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of the Reliability of Acupuncture Deqi Sensations in Knee Osteoarthritis

Abstract: Deqi is one of the core concepts in acupuncture theory and encompasses a range of sensations. In this study, we used the MGH Acupuncture Sensation Scale (MASS) to measure and assess the reliability of the sensations evoked by acupuncture needle stimulation in a longitudinal clinical trial on knee osteoarthritis (OA) patients. The Knee injury and Osteoarthritis Outcome Score (KOOS) was used as the clinical outcome. Thirty OA patients were randomized into one of three groups (high dose, low dose, and sham acupun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 36 publications
0
50
0
Order By: Relevance
“…Manual acupuncture emphasises the occurrence of “de-qi” feelings, which can be induced by proper and effective manual manipulation of the needle. The intensity of de-qi feelings plays a key role in the analgesic effects of manual acupuncture 35. The importance of manipulation of the needle is no less than that of the selection of the appropriate acupoint 36.…”
Section: Discussionmentioning
confidence: 99%
“…Manual acupuncture emphasises the occurrence of “de-qi” feelings, which can be induced by proper and effective manual manipulation of the needle. The intensity of de-qi feelings plays a key role in the analgesic effects of manual acupuncture 35. The importance of manipulation of the needle is no less than that of the selection of the appropriate acupoint 36.…”
Section: Discussionmentioning
confidence: 99%
“…The full details of subject enrollment and inclusion, study design, acupuncture procedures and fMRI acquisition are reported elsewhere ( Chen et al, 2014; Spaeth et al, 2013 ). Here we provide a brief description of the methods and focus on the procedures and analysis details relevant for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Each acupuncture session lasted approximately 25 min and was the same for all subjects, regardless of the group assignment. For the purposes of this analysis, subjects in the two verum acupuncture groups were combined, as the two treatment types evoked similar deqi sensation, had the same stimulation time and treatment effect, as indicated by KOOS ( Spaeth et al, 2013 ). Compared to verum acupuncture, in which the needle penetrates the skin, sham acupuncture was performed with non-penetrating Streitberger needles (the needle retracts up into the shaft when pressed against the skin).…”
Section: Methodsmentioning
confidence: 99%
“…The development of the ASS was based on McGill's Pain Questionnaire (MPQ) [21], the MASS on traditional Chinese medicine descriptions of de qi sensation [2, 6, 22], and the SNSQ on interviews with patients [23]. They have been validated for use in clinical acupuncture trials and physiological studies.…”
Section: Introductionmentioning
confidence: 99%